Mechanical regulation of T-cell functions - Chen, Wei; Zhu, Cheng (Immunological reviews, 2013)
Summary T cells are key players of the mammalian adaptive immune system. They experience different mechanical microenvironments during their life cycle, from the thymus, secondary lymph organs, and peripheral tissues that are free of externally applied force, but display variable substrate rigidities to the blood and lymphatic circulation systems, where complicated hydrodynamic forces are present. Regardless of whether T cells are subject to external forces or generate their own internal forces, they respond and adapt to different biomechanical cues to modulate their adhesion, migration, trafficking, and triggering of immune functions through mechanical regulation of various molecules that bear force. These include adhesive receptors, immunoreceptors, motor proteins, cytoskeletal proteins, and their associated molecules. Here, we discuss the forces acting on various surface and cytoplasmic proteins of a T cell in different mechanical milieus. We review existing data on how force regulates protein conformational changes and interactions with counter molecules, including integrins, actin, and the T‐cell receptor, and how each relates to T‐cell functions.